Therapeutic role of polyunsaturated fatty acids and of their derivatives in pathophysiological processes - N. V. Groza; A. B. Golovanov; E. A. Nalivayko; G. I. Myagkova (Тонкие химические технологии, 2012)
This review presents literature data on studies of the therapeutic role of natural polyunsaturated fatty acids and their derivatives in the processes of inflammation, cancer, and immune response.